Implementasi Manajemen Kelas dalam Meningkatkan Prestasi Belajar Siswa di SMKN 1 Cimerak - Deca Deca (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2025)
Class management is all efforts directed towards creating an effective and enjoyable learning atmosphere, as well as motivating students to learn to the best of their abilities. This research aims to understand how the implementation of class management can improve student achievement at SMKN 1 CIMERAK. The type of research in this study is qualitative research with a descriptive approach that uses data collection techniques including interviews, observations, open and directed discussions, as well as documentation studies involving the school principal and teachers of SMKN 1 CIMERAK to describe the implementation of class management in improving student performance at SMKN 1 CIMERAK. The results of the study show that the implementation of class management in improving student performance at SMKN 1 CIMERAK starts with teaching objectives, time management, room arrangement, and grouping students in learning.